What Goes Up Must Come Down? : House Price Dynamics in the United States - Klyuev, Vladimir (Washington, D.C. : International Monetary Fund, 2008)
This paper estimates the evolution of equilibrium real home prices in the United States and finds that despite recent declines, single-family homes remained 8 to 20 percent overvalued as of the first quarter of 2008. In the short run, the gap between actual and equilibrium prices does not exert powerful influence over price dynamics. Instead, that dynamics is driven by the inventory-to-sales ratio and by foreclosure starts in a highly inertial relationship. Taken together, this implies that price declines are likely to continue, including past the point where overvaluation is eliminated. The paper also finds that from the early 1990s onwards changes in regional home prices have been more synchronized than before, and that the recent movements in the average price index have reflected a nationwide housing boom, followed by a nationwide housing bust.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet